1995
DOI: 10.2105/ajph.85.2.240
|View full text |Cite
|
Sign up to set email alerts
|

The association between leisure-time physical activity and dietary fat in American adults.

Abstract: Relations between leisure-time physical activity and dietary fat were examined in a population-based probability sample of 29,672 adults in the 1990 Behavioral Risk Factor Surveillance System. Consumption of 13 high-fat food items and participation in physical activities were measured, and fat and activity scores were calculated. Dietary fat and physical activity were strongly and inversely associated. This association was independent of nine other demographic and behavioral risk factors. Etiologic researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 29 publications
4
49
2
Order By: Relevance
“…We did not find strong support for earlier findings that physically active subjects eat more fruits and vegetables (11)(12)(13) , have a higher intake of fibre (11,12) or lower intake of fat (11,12,14) . However, we found that intake of vitamin C was higher among the active than inactive cotwins, which is in line with some previous studies (11,12) .…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find strong support for earlier findings that physically active subjects eat more fruits and vegetables (11)(12)(13) , have a higher intake of fibre (11,12) or lower intake of fat (11,12,14) . However, we found that intake of vitamin C was higher among the active than inactive cotwins, which is in line with some previous studies (11,12) .…”
Section: Discussioncontrasting
confidence: 99%
“…We compared participants with missing or incomplete dietary data (nϭ89) with participants included in this study (nϭ268) along baseline measures of age, education, body mass index, ethnicity, and minutes on the treadmill. Participants with complete data were somewhat more educated than participants with incomplete data (15 Although we noted several differences between participants with complete vs. incomplete dietary data, the magnitude of the differences was fairly small and evident for 5 out of 15 variables.…”
Section: Sship-i Resultsmentioning
confidence: 60%
“…6 -10 Although the relationship between physical activity and diet has greatly interested epidemiologists and others, because of the role of both behaviors in some of the same chronic diseases (e.g., heart disease and some cancers), results from this body of literature have been inconsistent. 11 Results from cross-sectional studies examining whether physically active individuals have healthier diets than inactive individuals have been mixed, with some studies supporting a positive relationship [12][13][14][15][16][17] and others finding no relationship or a modest relationship. 2,3,18 -21 Few prospective studies have examined this issue.…”
Section: Introductionmentioning
confidence: 99%
“…In this context there are data to suggest that inactivity tends to cluster with other health behaviours such as less healthy dietary practices (Lytle et al 1995;Simoes et al 1995), cigarette smoking and alcohol use (Dannenberg et al 1989;Raitakari et al 1994;Lytle et al 1995), which may have an adverse effect on both the quantity and distribution of body fat. Since smoking and alcohol increase visceral fat Physical activity, energy expenditure, obesity 693 deposition (Troisi et al 1991), and inactivity is associated with increased body fat, the net effect of the covariance of inactivity with other health behaviours is to increase the risk of morbidity and mortality associated with obesity.…”
Section: Adultsmentioning
confidence: 99%